2022
DOI: 10.1002/mus.27641
|View full text |Cite
|
Sign up to set email alerts
|

Patient preference for virtual versus in‐person visits in neuromuscular clinical practice

Abstract: Introduction/Aims: It is unknown if patients with neuromuscular diseases prefer inperson or virtual telemedicine visits. We studied patient opinions and preference on virtual versus in-person visits, and the factors influencing such preferences.Methods: Telephone surveys, consisting of 11 questions, of patients from 10 neuromuscular centers were completed.Results: Five hundred and twenty surveys were completed. Twenty-six percent of respondents preferred virtual visits, while 50% preferred in-person visits. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Current literature suggests an increasing demand for web-based consultations [63][64][65][66]. On the basis of this evidence, it is reasonable and efficient to equip undergraduates in communication skills training for health care professionals with the possibility to practice with virtual patient-health care provider encounters.…”
Section: Web-based Consultationsmentioning
confidence: 99%
“…Current literature suggests an increasing demand for web-based consultations [63][64][65][66]. On the basis of this evidence, it is reasonable and efficient to equip undergraduates in communication skills training for health care professionals with the possibility to practice with virtual patient-health care provider encounters.…”
Section: Web-based Consultationsmentioning
confidence: 99%
“…Este manejo, como se ha mencionado, puede ser en forma presencial o a través de sesiones virtuales, en México y con datos no publicados, se cuenta con la experiencia de médicos rehabilitadores que han hecho uso de las sesiones virtuales para tratar y dar seguimiento a pacientes con COVID persistente y con buenos resultados, esto abre la posibilidad de implementar las sesiones a distancia para el manejo y control de ciertas patologías que afectan el área musculoesquelética, pues es sabido que muchos pacientes prefieren la privacidad que brinda una sesión virtual, además de la comodidad del uso de la tecnología, lo que probablemente incremente la telemedicina en algunos campos. 7 Este tema tan interesante y muchos más serán presentados en el XXVII Congreso Mexicano de Medicina Física y Rehabilitación y 4to. Congreso Internacional «Actualización en Rehabilitación» a celebrarse en la ciudad de Mérida, Yucatán del 21 al 24 de septiembre del presente año, por lo que te invitamos a inscribirte y compartir experiencias.…”
Section: The Persistent Covid or Long-covid: A New Field Of Action Fo...unclassified
“…One of the main problems reported by patients during similar virtual visits organized during the COVID-19 pandemic was the lack of face-to-face communication and clinical examination, with most preferring a face-to-face visit or at least video communication [ 10 ]. In another study, patients indicated that interactions during a face-to-face visits were of high personal importance [ 11 ]. Another study that examined patient satisfaction and experiences with virtual visits found that technical difficulties were associated with lower overall satisfaction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%